Coconut waste biodiesel: Comparison of acid and alkaline catalyst - Sulaiman, Sarina; Abdul Raman , Abdul Aziz; Aroua, Mohammed Kheireddin (2010)
Biodiesel industry requires a cheaper and economical viable raw material that can replace the vegetable oil. Waste from animal and plant sources became the main option due the availability and cheap. In this study, coconut waste is used to produce biodiesel using methanol, acid sulfuric and KOH. In situ process is used, where all the catalyst, reagent and raw material is mixed together in one system. The highest yield, 90% is achieved with 5 wt% of KOH within 3 hr by mixing raw material and methanol. Acid sulfuric catalyzed process took a longer reaction time and higher amount of catalyst is needed.